FUNDING COMPATIBILITY OF THE HALAL INDUSTRY BASED ON THE ABNORMAL RATE OF ISSI STOCK RETURN - Nurul Susianti; Shofia Mauizotun Hasanah; Intan Kusuma Pratiwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article aims to test the suitability of sharia funding by referring to the MUI Fatwa on the halal industry in the Indonesian capital market with a benchmark of sharia compliance based on. Event study before and after the Covid-19 pandemic, where the focus of the problem and the hypothesis of this research is on whether there is a change in the level of abnormal Return of the 30 ISSI stock samples. Observations were made before the government's announcement about Covid-19 pandemic, which was around the end of january 2020 and after entering the new normal, which was around the beginning of August 2020. The results of this study indicate that the significant figures both before and after the Covid-19 pandemic on ISSI sharia shares are less than 0.05, which means that ISSI shares do not have abnormal returns, so the research results are in line with the MUI Fatwa Article 5 concerning Securities Transactions. Article 5 discusses transaction mechanisms that are not allowed such as gharâr, maysîr, usurî, and risywah speculating and manipulation. To be appropriate because what is meant by abnormal returns in the capital market is often influenced by speculation and manipulation so that prices are no longer reasonable. The research hypothesis is rejected as an alternative to continuously to trust investor funding in the Indonesian islamic capital market industry.